Adverse effects of BMPR2 suppression in macrophages in animal models of pulmonary hypertension. (1st March 2020) - West, James; Chen, Xinping; Yan, Ling; Gladson, Santhi; Loyd, James; Rizwan, Hamid; Talati, Megha
Abstract : Inflammatory cells contribute to irreversible damage in pulmonary arterial hypertension (PAH). We hypothesized that in PAH, dysfunctional BMPR2 signaling in macrophages contributes to pulmonary vascular injury and phenotypic changes via proinflammatory cytokine production. Studies were conducted in: (1) Rosa26‐rtTA2 3 X TetO7‐Bmpr2delx4 FVB/N mice (mutant Bmpr2 is universally expressed, BMPR2 delx4 mice) given a weekly intra‐tracheal liposomal clodronate injections for four weeks; and (2) LysM‐Cre X floxed BMPR2 X floxed eGFP monocyte lineage‐specific BMPR2 knockout (KO) mouse model (Bmpr2 gene expression knockdown in monocytic lineage cells) (BMPR2 KO ) following three weeks of sugen/hypoxia treatment. In the BMPR2 delx4 mice, increased right ventricular systolic pressure (RVSP; P  < 0.05) was normalized by clodronate, and in monocyte lineage‐specific BMPR2 KO mice sugen hypoxia treatment increased ( P  < 0.05) RVSP compared to control littermates, suggesting that suppressed BMPR2 in macrophages modulate RVSP in animal models of PH. In addition, in these mouse models, muscularized pulmonary vessels were increased ( P  < 0.05) and surrounded by an increased number of macrophages. Elimination of macrophages in BMPR2 delx4 mice reduced the number of muscularized pulmonary vessels and macrophages surrounding these vessels. Further, in monocyte lineage‐specific BMPR2 KO mice, there was significant increase in proinflammatory cytokines, including C‐X‐C Motif Chemokine Ligand 12 (CXCL12), complement component 5 a (C5a), Interleukin‐16 (IL‐16), and secretory ICAM. C5a positive inflammatory cells present in and around the pulmonary vessels in the PAH lung could potentially be involved in pulmonary vessel remodeling. In summary, our data indicate that, in BMPR2‐related PAH, macrophages with dysfunctional BMPR2 influence pulmonary vascular remodeling and phenotypic outcomes via proinflammatory cytokine production.